Pengaruh Teknik Budidaya SRI (System of Rice Intensification) dan Legowo Terhadap Iklim Mikro dan Produktivitas Padi Ketan (Studi Kasus di Subak Sigaran) - Sanjaya, I Putu; Tika, I Wayan; Sumiyati, Sumiyati (Jurnal BETA (Biosistem dan Teknik Pertanian); Vol 2 No 1 (2014): Maret, 2014)
This study was conducted to determine the effect of planting System of Rice Intensification (SRI) and legowo 6:1 row planting system of the microclimate and the rice plants productivity. This study was divided into 4 treatments with 3 replications, ie treatments conventional techniques, SRI method of planting, application of legowo 6:1 row planting system, and combination of SRI planting method and legowo 6:1 row planting system. The results showed the application of SRI planting method and legowo 6:1 row planting system not affecting the microclimate conditions, but affecting the productivity of rice plants. The results also showed that treatment K3 applying SRI methods combined with legowo 6:1 row planting system is the best treatment compared with other treatments.
Keywords: SRI, legowo, microclimate, rice plants productivity